Coming to terms with it all: Adult burn survivors’ ‘lived experience’ of acknowledgement andacceptance during rehabilitation - Kornhaber, R.; Wilson, A.; Abu-Qamar, Ma'en; McLean, L. (Pergamon Press, 2014)
Although studies have explored the ‘lived experience’ of burn survivors, little is known about their experiences encountered during rehabilitation. A descriptive phenomenological study was conducted to gain an in-depth insight into burn survivors’ experiences’ of acknowledgement and acceptance of their injury and the challenges experienced during their rehabilitation journey. A descriptive phenomenological methodology was used to construct themes depicting how burn survivors endeavoured to acknowledge and accept their injury and subsequent altered body image. Twenty men and one woman up to eight years after-burn within Australia were selected through purposeful sampling, and data were collected through in-depth individual interviews conducted in 2011 (N = 21). Interviews were analysed using Colaizzi's method of data analysis. The emergent theme acknowledgement identified four cluster themes that represented how burn survivors came to terms with their injury and an altered body image: (1) reasoning (2) humour (3) the challenge of acceptance (4) self-awareness. Coming to terms with a severe burn is a challenging experience. Reasoning and humour are strategies utilised by burn survivors that facilitate with acknowledgement and acceptance. Understanding these concepts through the burn survivors’ perspective will, potentially, facilitate a better understanding of how to best provide for this cohort of patients.